1999
DOI: 10.1023/a:1026434732031
|View full text |Cite
|
Sign up to set email alerts
|

The high-dose sequential (Milan) chemotherapy/PBSC transplantation regimen for patients with lymphoma is not cardiotoxic

Abstract: The HDS chemotherapy regimen produced no significant sign of cardiotoxicity up to one year after transplantation in patients with normal baseline cardiac function and no history of cardiac disease, pretreated with up to 550 mg/m2 of doxorubicin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
7
0
2
Order By: Relevance
“…10 However, in recent years, the percentage of patients receiving singleagent HD cyclophosphamide up to 7 g/m 2 or 200 mg/kg experiencing cardiotoxicity has diminished to nearly zero with the adoption of multifractionated schedule of administration. 4,5,[7][8][9]25 Available evidence indicates that singleagent HD cyclophosphamide-associated cardiac toxicity is dose and schedule dependent, and it is not related to the cumulative drug dose. 13,16,21 No pharmacokinetic parameter has been consistently associated with cardiotoxicity, although a significant inverse association between a reduced HD cyclophosphamide area under the curve (AUC) (ie accelerated clearance due to an increased conversion to active metabolites) and cardiotoxicity was found in three independent studies, 17,26,27 but not confirmed in a larger one.…”
Section: Cardiac Toxicity Due To Conditioning Regimenmentioning
confidence: 99%
See 3 more Smart Citations
“…10 However, in recent years, the percentage of patients receiving singleagent HD cyclophosphamide up to 7 g/m 2 or 200 mg/kg experiencing cardiotoxicity has diminished to nearly zero with the adoption of multifractionated schedule of administration. 4,5,[7][8][9]25 Available evidence indicates that singleagent HD cyclophosphamide-associated cardiac toxicity is dose and schedule dependent, and it is not related to the cumulative drug dose. 13,16,21 No pharmacokinetic parameter has been consistently associated with cardiotoxicity, although a significant inverse association between a reduced HD cyclophosphamide area under the curve (AUC) (ie accelerated clearance due to an increased conversion to active metabolites) and cardiotoxicity was found in three independent studies, 17,26,27 but not confirmed in a larger one.…”
Section: Cardiac Toxicity Due To Conditioning Regimenmentioning
confidence: 99%
“…47,48 HD mitoxantrone is commonly used as part of conditioning regimens not including HD cyclophosphamide, where its acute and long-term cardiac toxicity has been acceptable in a large series of patients. 7,9,49,50 However, in one report, four out of six patients with no pre-existing cardiac disease experienced severe cardiac toxicity with two treatment-related deaths following administration of cyclophosphamide 2.4 g/m 2 (an 'intermediate' dose not associated with cardiac toxicity) and mitoxantrone 35-45 mg/m 2 . 47 In another study, administration of HD cyclophosphamide at the maximum tolerated dose (ie 200 mg/kg) divided into only two daily fractions may have played a role in determining a 25% incidence of CHF with one treatment-related death, besides the potential contribution of HD mitoxantrone in patients previously exposed to anthracyclines.…”
Section: Cytarabinementioning
confidence: 99%
See 2 more Smart Citations
“…Although cardiac dysfunction is well described with other alkylating agents such as cyclophosphamide, 6 single-agent melphalan has not been shown to affect cardiac contractility in prospective studies. 7 Fludarabine has also only been rarely associated with cardiac dysfunction, with a single report of non-fatal congestive heart failure in two of 27 patients treated for chronic lymphocytic leukaemia. 8 Conditioning regimens combining fludarabine and melphalan have been associated with veno-occlusive disease and mucosal toxicity, but development of cardiotoxicity had not been specifically assessed in earlier reports.…”
mentioning
confidence: 99%